Analysis of Noise Characteristics of Multichannel Systems of the Formation of Signals of Georadars with Synthesized Aperture - Oleg R. Kuzichkin; Dmitriy I. Surzhik; Gleb S. Vasiliev; Igor A. Kurilov; Nikolai V. Dorofeev (Active and Passive Electronic Components)
The noise characteristics of multichannel systems of forming signals based on hybrid frequency synthesizers with automatic compensation of phase distortions of direct digital synthesizers, which are used in the composition of georadars with synthesized aperture, are investigated. It is established that the phase noise of the output signals of the formers at the 1 kHz detuning from the carrier oscillation at the output frequencies of the devices in the range from 500 to 3500 MHz is characterized by a level of minus 100 - minus 130 dB. In this case, the circuit of the signal former based on a hybrid frequency synthesizer with direct digital synthesizer as a reference oscillator of a phase locked loop is characterized by the worst noise characteristics but with the highest degree of autocompensation (about 13 dB). Conversely, the circuit of the signal former based on a hybrid frequency synthesizer with direct digital synthesizer as a support generator of the phase-locked loop has the best phase noises level from the considered variants of devices and least degree of autocompensation (about 6 dB).